PERAN GREEN MARKETING DAN CORPORATE SOCIAL RESPONSIBILITY DALAM MENINGKATKAN MINAT BELI MEREK HIJAU - Sutisna, Sutisna; Wiguna, Wahyu (Bussman Journal : Indonesian Journal of Business and Management, 2024)
Many people are increasingly liking environmentally friendly products because they are considered not to pollute the environment in every production and marketing process. Public awareness of the environment is increasing, requiring companies to adapt to these demands. This study aims to find out whether eco-friendly marketing and corporate social responsibility (CSR) programs directly or indirectly affect purchase intent on green products mediated by green brand image. The design of the study was a cross-sectional survey with a total of 200 respondents. The sampling technique used is regional sampling based on districts/cities in Banten province. The data analysis method uses a structural equation model using SMART-PLS. The results of the study show that green marketing and CSR play a significant role in increasing consumer buying interest. This study provides insight into the importance of marketing managers in designing green marketing programs more appropriately to be able to increase consumer buying interest in green brands